(untitled) (Global Business Management Review (GBMR), 2023)
Nowadays, due to the rapidly changing business environment, non-technical skills have become critical factors in determining employment. Companies assert that fresh graduates often fall short of their expectations. Nevertheless, employers emphasize that non-technical skills are crucial for fresh graduates to remain competitive and secure employment in the current job market. Therefore, this research aims to study the importance of non-technical skills and their impact on graduates’ employability. The study utilizes online questionnaire surveys for 120 graduates from different states, universities, occupations, and backgrounds to rank the importance of 15 non-technical skills. Meanwhile, Pearson correlations and multiple regression analysis are employed to study the relationship between three independent variables and graduates’ employability. The statistical findings reveal a positive correlation between non-technical skills and graduates’ employment. According to the study results, the top five skills deemed more important than others are adaptability, ethical behavior, leadership, critical and creative thinking, and tolerance of ambiguity. Therefore, it is essential for students to develop their non-technical skills during their studies to meet the expectations of future employers.